Optimizing anti‐T‐lymphocyte globulin dosing to improve long‐term outcome after unrelated hematopoietic cell transplantation for hematologic malignancies. Issue 3 (16th November 2019) - Turki, Amin T.; Klisanin, Vesna; Bayraktar, Evren; Kordelas, Lambros; Trenschel, Rudolf; Ottinger, Hellmut; Steckel, Nina K.; Tsachakis‐Mück, Nikolaos; Leserer, Saskia; Ditschkowski, Markus; Liebregts, Tobias; Koldehoff, Michael; et al.
Abstract : Prophylaxis of graft‐versus‐host disease (GVHD) after allogeneic hematopoietic stem cell transplantation (HCT) remains challenging. Because prospective randomized trials of in‐vivo T cell depletion using anti‐T‐lymphocyte globulin (ATLG) in addition to a calcineurin inhibitor and methotrexate (MTX) led to conflicting outcome results, we evaluated the impact of ATLG on clinical outcome, lymphocyte‐ and immune reconstitution survival models. In total, 1500 consecutive patients with hematologic malignancies received matched unrelated donor (MUD) HCT with cyclosporin and MTX (N = 723, 48%) or with additional ATLG (N = 777, 52%). In the ATLG cohort, grades III‐IV acute (12% vs 23%) and extensive chronic GVHD (18% vs 34%) incidences were significantly reduced ( P < .0001). Nonrelapse mortality (27% vs 45%) and relapse (30% vs 22%) differed also significantly. Event‐free and overall survival estimates at 10 years were 44% and 51% with ATLG and 33% and 35% without ATLG ( P < .002 and <.0001). A dose‐dependent ATLG effect on lymphocyte‐ and neutrophil reconstitution was observed. At ATLG exposure, lymphocyte counts and survival associated through a logarithmically increasing function. In this survival model, the lymphocyte count optimum range at exposure was between 0.4 and 1.45/nL ( P = .001). This study supports additional ATLG immune prophylaxis and is the first study to associate optimal lymphocyte counts with survival after MUD‐HCT. Abstract : While the role of anti‐T‐lymphocyte globulin as graft‐versus‐host disease prophylaxis in allogeneic cell transplantation recipients is controversial, Turki et al show a long‐term outcome benefit in a large patient cohort and present a novel model associating optimum lymphocyte counts at anti‐T‐lymphocyte globulin exposure with improved survival.